Evidence for persisting with treatment with paracetamol in patients with mild to moderate osteoarthritis of the knees - Chin, C.Y.; Khartoum, R.; Mohamed, M.; Hanafi, N.S.; Jenn, N.C. (2012)
Although paracetamol is recommended as first line pharmacological therapy for mild to moderate osteoarthritis (OA) of the knees, it is deemed to be not as efficacious as other pharmacological agents. One of the reasons could be due to poor adherence and persistence to therapy. This study examines the efficacy of the early response and the response after four weeks to paracetamol in mild to moderate OA of the knees in daily clinical practice. This is an open label study. Consecutive patients with mild to moderate OA of the knees were given 1.3 grams extended-release paracetamol three times per day for 4 weeks. Pain based on the Western Ontario and McMaster Universities (WOMAC) v3 VAS osteoathritis index was used as a measure of efficacy. Serial liver and renal profiles were done for safety monitoring. An early assessment of efficacy was done at week 1 and a later at the end of 4 weeks of therapy. The primary efficacy endpoint was a 30 reduction in global pain score at week 4 compared to baseline Analysis was done using the SPSS Version 18. Thirty patients entered the study. 73.3 were females. Mean age, BMI and duration of OA was 58.5years (SD +/- 6.9), 28.1 kg/m2 (SD +/- 6.4) 22.8 (SD +/- 32.2) months respectively. The mean VAS WOMAC at baseline for pain was 35.4mm (SD +/- 17.5). At the end of the first week of therapy, there was no difference in the WOMAC pain score compared to baseline. (95 CI -0.54-12.1, p=0.07). However by the end of 4 weeks there was a statistically significant 46.6 (95 CI 27.6-72.6, p<0.001) reduction in global pain compared to baseline. An absolute reduction of 16.5mm in global pain (95 CI 9.9-23.0, p<0.001) compared to baseline was also seen. No serious adverse events were encountered. Paracetamol used to treat OA of the knees is not efficacious in the first week of therapy. However persistence with therapy for a further three weeks results in significant reduction in pain. Therefore every effort should be made to ensure persistence with the recommended full four weeks of treatment. Chia Yook Chin, Rabia Khartoum, Mohazmi Mohamed, Nik Sherina Hanafi, Ng Chirk Jenn. Evidence for Persisting with Treatment with Paracetamol in Patients with Mild to Moderate Osteoarthritis of the Knees. Life Sci J 2012;9(3):1131-1137]. (ISSN: 1097-8135). http://www.lifesciencesite.com. 157